Kurdish Insurgents and Postgeneration: „Big Village” as an Interactive Memory Work - Fatma Edemen (Kwartalnik Filmowy, 2024)
The Kurdish people, lacking a sovereign state of their own, reside within the boundaries of Turkey, Iran, Iraq, and Syria, where they are subjected to the rules and identities of these nations, often facing restrictions on their cultural expression. This situation has disabled their entry into the filmmaking, with documentaries becoming their preferred medium due to its cost-effectiveness and simpler technical demands. These documentaries typically delve into the Kurds’ painful historical experiences. Big Village (2020), directed by Beri Shalmashi and Lyangelo Vazquez, stands out as the first Kurdish interactive web documentary (i-doc). It intricately weaves personal and social narratives, focusing on several families and a Kurdish insurgent group from Eastern Kurdistan. The i-doc explores the stories of the former residents of Gewredê, a village that has since vanished. It uniquely blends old photos and video clips to craft its narrative. This study aims to analyse Big Village through the lens of the insurgents’ memories, the inherited memories of their children, and the use of archival materials, examining how an interactive documentary can effectively communicate historical traumas to modern viewers.